A New Type of Weakly Commutative Groups - Ibrahim, Hariwan Z.; Salih, Muwafaq M. (Science Journal of University of Zakho, 2017)
The aim of the present paper is to define and study a new class of groups, namely Wm-groups with a single binary operation based on axioms of semi commutativity, right identity and left inverse. Moreover, we introduce the notions of right cosets, quotient Wm-groups, homomorphisms, kernel and normal Wm-subgroups in terms of Wm-groups, and investigate some of their properties.